Remodelling of human bone on the chorioallantoic membrane of the chicken egg: De novo bone formation and resorption. (9th August 2018) - Moreno‐Jiménez, Inés; Lanham, Stuart A.; Kanczler, Janos M.; Hulsart‐Billstrom, Gry; Evans, Nicholas D.; Oreffo, Richard O.C.
Abstract: Traditionally used as an angiogenic assay, the chorioallantoic membrane (CAM) assay of the chick embryo offers significant potential as an in vivo model for xenograft organ culture. Viable human bone can be cultivated on the CAM and increases in bone volume are evident; however, it remains unclear by what mechanism this change occurs and whether this reflects the physiological process of bone remodelling. In this study we tested the hypothesis that CAM‐induced bone remodelling is a consequence of host and graft mediated processes. Bone cylinders harvested from femoral heads post surgery were placed on the CAM of green fluorescent protein (GFP)‐chick embryos for 9 days, followed by micro computed tomography (μCT) and histological analysis. Three‐dimensional registration of consecutive μCT‐scans showed newly mineralised tissue in CAM‐implanted bone cylinders, as well as new osteoid deposition histologically. Immunohistochemistry demonstrated the presence of bone resorption and formation markers (Cathepsin K, SOX9 and RUNX2) co‐localising with GFP staining, expressed by avian cells only. To investigate the role of the human cells in the process of bone formation, decellularised bone cylinders were implanted on the CAM and comparable increases in bone volume were observed, indicating that avian cells were responsible for the bone mineralisation process. Finally, CAM‐implantation of acellular collagen sponges, containing bone morphogenetic protein 2, resulted in the deposition of extracellular matrix and tissue mineralisation. These studies indicate that the CAM can respond to osteogenic stimuli and support formation or resorption of implanted human bone, providing a humanised CAM model for regenerative medicine research and a novel short‐term in vivo model for tissue engineering and biomaterial testing.